Low Seroprevalence of Brucella Spp. among Remote Colombian Communities from the Sierra Nevada De Santa Marta - Oakley, Regina; Kann, Simone; Plag, Michèle; Concha, Gustavo; Dreyfus, Anou; H. Paris, Daniel (International Journal of Negative Results, 2023)
Brucella species cause a high burden of disease globally, infecting both humans and animals; however, One Health has been under-appreciated in Colombia. This study aimed to determine the seroprevalence of Brucella spp. in two remote indigenous communities from the Sierra Nevada de Santa Marta, Colombia. These communities live in close contact with their livestock, indicating a potential susceptibility to zoonotic pathogens. The livestock routinely kept by these communities include cattle, small ruminants and pigs, the known hosts of human pathogenic Brucella spp.. A low level of exposure to Brucella spp. was documented, with only one positive participant among 539 participants (0.2%; 95% CI 0.0 – 1.0). Nevertheless, due to the high risk that zoonoses pose, we recommend discussions with the community for the potential establishment of One Health surveillance studies for the early detection and prevention of future zoonotic disease threats.
Keywords: Brucellosis; Brucella spp.; zoonosis; seroprevalence; Colombia